Луцьк радянський: соціокультурний простір - Хлібовська, Ганна Миколаївна; Khlibovska, Аnna M. (Східноєвропейський національний університет ім. Лесі Українки, 2014)
У статті проаналізовано соціокультурний розвиток міста Луцька за радянської доби. Розкривається вплив урбанізаційних процесів на побут населення, духовний клімат, формування та утвердження нового світогляду і моделей поведінки міського жителя. Акцентується увага на методах усталення радянського способу життя. General overview of socio-cultural development of Volyn region centre – city Lutsk – in Soviet period covering 1945 – 1991 is represented. The author analyzes influence of urban processes on daily lives of townspeople, spiritual environment of Soviet town, forming of new worldview and establishment of new behavior models of townsfolk. Special attention is paid to methods of introduction of Soviet lifestyle. It is established, that in Lutsk a system of general influence over personality was formed, which used mass media, educational institutions, public organizations, whose activity was strictly controlled by communist party structures. At the same time some problems – such as communal services, housing problem, medical service – were not entirely solved. Such topics as emergence and existence of urban subcultures and changes in ethnic and social structure of Lutsk deserve further investigation.
Soviet Lutsk: socio-cultural space
Keywords: Луцьк; соціокультурний розвиток; урбанізація; радянський період; міське середовище; містяни; духовне життя; Lutsk; socio-cultural development; urbanization; Soviet period; urban environment; townspeople; spiritual life